Acceptance of Banking Information Technology in PT BNI of Makassar - Muchran, Muchriana (Journal of Economics and Behavioral Studies, 2015)
Various advantages offered by the use of internet banking, but some customers are still associated with conventional ways of doing that is through ATM transactions or queue. The research aimed to analyze trust, perceived ease of use, perceived usefulness and experience to intention to use internet banking. This research was conducted in PT BNI of Makassar. The data were obtained using questionnaire given to customers. The populations were customers of BNI Bank listed as service users of Internet banking. The sample was selected using simple random sampling technique. Hypotheses tested use of Partial Least Square (PLS) method by means of AMOS program. The results of the research indicate that among the eight hypotheses, four of them are significant, while the other four not significant. Trust has significant to perceived ease of use. Trust does not have significant to perceived usefulness. Trust has significant to intention to use internet banking. Perceived ease of use has significant to perceived usefulness. Perceived ease of use does not have significant to intention to use internet banking. Perceived usefulness does not significant to intention to use internet banking. Perceived ease of use has significant relationship with intention to use internet banking modernized by experience. Perceived usefulness does not have significant relationship with intention to use internet banking modernized by experience.